The Students’ Perceptions in Using Youtube as Media to Enrich English Speaking Skill - Muhammad Amzah M.A.A (Institut Agama Islam Negeri Palopo, 2022)
In order to create effective teaching-learning process teacher must find appropriate method and media. Lately, the use of technology as a media in teaching-learning process has become a very common thing to do. Nowadays, YouTube is one of the social media platform that most used in teaching-learning process. This study aims to find out how does the teacher use YouTube in teaching English speaking skill at SMK Miftahussalam and also how is the students’ perception in using YouTube as media to Enrich English speaking skill at SMK Miftahussalam. The design of this research was qualitative. The subjects that has examined in this research are teacher and students of SMK Miftahussalam. The findings show that not all of the material/chapters are suitable to use YouTube as the media, so the teacher must determines whether the material is suitable or not. Then, the teacher searches for the most attractive video. Then, the teacher bought a link to the students. After the students watch the video, the teacher starts the discussion also question and answer section. Then, the students are asked to practice the material by themselves. The findings also show that most students think that the use of YouTube in learning speaking is very important, especially to learn how to pronounce a word. Furthermore, YouTube can be used as a learning media that can support student learning success because there are various kinds of videos about education (on it). It shows that the use of YouTube as media to enrich the students speaking skills is worth it. The use of YouTube helps the students to enrich their students speaking skills, especially in terms of pronunciation and vocabulary.